Perancangan Modul Trainer Interface Mikrokontroler Berbasis ESP32 Sebagai Media Pembelajaran Pada Mata Kuliah Embedded System - Rafika, Ageng Setiani; Febriyanto, Erick; Safriyati, Evi (Technomedia Journal, 2020)
Embedded system courses in the department of informatics engineering there are materials taught in the form of microcontroller interfacing techniques that use three types of interface protocols on peripheral microcontroller communication microcontrollers that can be programmed, and designed specifically for embedded systems. The learning process in this subject is the lecturer conveying the theories and concepts of the microcontroller interface by illustrating the concept only on the board. Of course, for some students who do not understand the concept of a microcontroller, it will be difficult to understand the material being taught. This study uses the design method then the method of observation and observation regarding the learning process in the interfacing course and interviewing several students about their understanding of the material being taught. This trainer will later be used as a student practicum tool to apply interfacing material to the Internet of Things-based microcontroller and its components directly along with programming techniques so that students who use this trainer in interfacing courses will get a theoretical understanding and its application to the microcontroller.